The best of I-Witness, volume 1 - Taruc, Jose Reyes III; David, Kara S.; Aguinaldo, Sandra S.; Severino, Horacio (GMA Network, 2005)
Collection of best episodes of I witness, a documentary television show in the Philippines by GMA Network. This volume describes the life of the people in sanitary landfills or dump sites, "Lola Isiang" one of the last remaining binukots or Panay-Bukidnon tribe princess, safari travel to Caribou, Kenya, the hardship of tuna fishing and the Aytas - 10 years after the eruption of Mt. Pinatubo.